Thickened carotid intima media thickness and carotid atherosclerosis among lupus nephritis patients : the role of traditional and lupus-specific factors. - Shaharir, Sazliyana; Kong, N. C.; Mohamed Said, Mohd. Shahrir; Tan, Hui Jan; Basri, Hamidon; M. T., Azmi (Wiley, 2011)
AIM: The objectives of this study were to investigate the frequency of thickened carotid intima media thickness (CIMT) and atherosclerosis among lupus nephritis (LN) patients and to study their associated risk factors. METHOD: In this cross-sectional study, carotid ultrasonography was performed on consecutive LN patients to determine CIMT and presence of carotid plaques. CIMT was considered to be abnormally thickened if it was more than the 75th percentile matched for age and sex from the 'Carotid Atherosclerosis Progression Study'. The association between thickened CIMT with traditional cardiovascular risk factors and lupus characteristics were examined. A total of 83 patients with the mean age of 33.6 ± 10 years were recruited. RESULTS: Fourteen patients (16.9%) had thickened CIMT and three (3.6%) had carotid plaques. On univariate analysis, traditional risk factors significantly associated with thickened CIMT (P < 0.05) were patient's current age, diabetes mellitus and waist circumference. Meanwhile, a lower serum C4 levels and higher serum C-reactive protein levels were the lupus-specific factors associated with thickened CIMT (P < 0.05, P < 0.05 and P < 0.01, respectively). In logistic regression analysis, the independent predictors of thickened CIMT were age of diagnosis, lower serum C4 levels and waist circumference (P < 0.05). CONCLUSION: More lupus specific factors were independently associated with thickened CIMT, suggesting that a multi-targeted approach of treatment addressing both the lupus and traditional cardiovascular risks are very important. Larger prospective studies of these special risk factors are indicated.